PENYELENGGARAAN KEWENANGAN DESA ADAT (Studi Kasus di Desa Kanekes Suku Baduy Kabupaten Lebak Provinsi Banten) - Rusito Rusito (LPPM STIA Banten, 2017)
Implementation of Law no. 6/2014 concerning Villages is characterized by increased village authority and village budgets including customary villages. In customary villages, the use of the village budget should be carried out in accordance with the customs and traditions prevailing in the village. However, because the regulations governing traditional villages are incomplete, there are still problems in implementing village authority in Kanekes Village and allocating budgets to carry out activities in accordance with local customary conditions. This paper describes the implementation of village authority in the Kanekes customary village of the Baduy tribe and the various problems that occur. The conclusion of this writing is that the implementation of authority based on rights of origin in Kanekes Village has been carried out in accordance with customary law, however local village-scale authority covering the field of village government administration, the field of implementation of village development, the field of community development and the field of community empowerment has not been fully carried out in accordance with the provisions. custom. The implementation of traditional village authority and budget allocation must be guided by applicable customary law so that in the future it does not cause negative impacts, namely threatening the preservation of Baduy traditional values ​​and state financial inefficiency.